Analisis Tingkat Kesulitan Soal Pemecahan Masalah dalam Buku Siswa Pelajaran Matematika SMP Kelas VII Kurikulum 2013 - Wulandari, Rika, Idris Harta, M.A., Ph. D (2017)
This study aims to analyze and describe the level of difficulty of problem solving item mathematics in terms of the components of the matter: type of problem, type of cardinal numbers, type of operation, the kind of operations, the kind of questions, data adequacy, and similarities with the previous question in the students book mathematics Junior High School 7th grade Curriculum 2013. This research uses qualitative research. Data collection method used is observation on each sample question and documentation. Data analysis techniques use the flow of data reduction steps, data presentation, and conclusion. The results showed: 1) There were 582 problem solving questions or about 33,64% of the 1730 items; 2) The type of problem solving question 69,93% dominant routine; 3) The type of dominant number of counting numbers as much as 70,45%; 4) Type of operations using more multiplication as much as 44,16%; 5) Many dominant operations use more than one operation as much as 59,80%; 6) Many dominant questions using one question as much as 81,44%: 7) Have a complete data sufficiency of 87,80%; 8) 69,42% questions is not similar to the previous questions. So the problem solving questions is categorized as having medium difficulty level.